Above and below the surface: Genetic and cultural factors in the development of values - Dellantonio, Sara (2017)
In the Attitude–Scenario–Emotion (ASE) model, social relationships are subpersonnally realized by sentiments: a network of emotions/attitudes representing relational values. We discuss how relational values differ from moral values and raise the issue of their ontogeny from genetic and cultural factors. Because relational values develop early in life, they cannot rely solely on cognition as suggested by the notion of attitude.